Desert God [compact disc, unabridged] : a novel of ancient Egypt - Smith, Wilbur A. (Smith, Wilbur A. Ancient Egypt series., 2014)
On the gleaming banks of the Nile, the brilliant Taita-slave and advisor to the Pharaoh-finds himself at the center of a vortex of passion, intrigue, and danger. His quest to destroy the Hyksos army and form an alliance with Crete takes him on an epic journey up the Nile, through Arabia and the magical city of Babylon, and across the open seas.